Quantum lattice representation for the curl equations of Maxwell equations. Issue 1 (1st February 2022) - Vahala, George; Hawthorne, John; Vahala, Linda; Ram, Abhay K.; Soe, Min
Abstract : A quantum lattice representation (QLA) is devised for the initial value problem of one-dimensional (1D) propagation of an electromagnetic disturbance in a scalar dielectric medium satisfying directly only the two curl equations of Maxwell. It si found that only 4 qubits/node are required. The collision, streaming, and potential operators are determined so as to recover the two curl equations to second order. Both polarizations are considered.